2013
DOI: 10.4293/108680813x13654754534594
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Repair of Giant Paraesophageal Hernias

Abstract: This report suggests that robotic repair of giant para-esophageal hernia has a lower recurrence rate than standard laparoscopic methods, but complications and mortality are similar to standard laparoscopic approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 30 publications
1
23
0
8
Order By: Relevance
“…In a series of 19 patients, Seetharamajah et al . reported similar times (Mean 184.5 ± 96.2 min) and preferentially used biological mesh in the majority of cases without a fundoplication . There was one conversion to an open repair in a patient who presented emergently with compromise of the gastric wall requiring partial gastrectomy.…”
Section: Discussionmentioning
confidence: 84%
“…In a series of 19 patients, Seetharamajah et al . reported similar times (Mean 184.5 ± 96.2 min) and preferentially used biological mesh in the majority of cases without a fundoplication . There was one conversion to an open repair in a patient who presented emergently with compromise of the gastric wall requiring partial gastrectomy.…”
Section: Discussionmentioning
confidence: 84%
“…They compared 12 patients who underwent para‐oesophageal HH repair using a robot with 17 and 13 patients who underwent conventional laparoscopic and open repair, respectively. Along the same lines, Seetharamaiah et al , in a recent retrospective series of 19 cases with GHH, state that robotic GHH repair is not different from the laparoscopic approach in terms of mortality and complications rate, but seems to be associated with a lower recurrence rate. However, these studies had some limitations: they were not prospective trials, there was limited information about the HH diameters or subtypes and there were no mid‐term follow‐up results.…”
Section: Discussionmentioning
confidence: 93%
“…In a reported series of 40 patients with para-oesophageal HH that included 13 patients with GHH, Draaisma et al (15) suggested that the robot-assisted approach was effective, associated with very low postoperative morbidity and accompanied by satisfactory symptomatic and anatomical radiological outcomes during a follow-up period of at least 1 year. They showed a mean operative time of 134 min, a 10% conversion rate, a 12.5% postoperative morbidity rate (17), in a recent retrospective series of 19 cases with GHH, state that robotic GHH repair is not different from the laparoscopic approach in terms of mortality and complications rate, but seems to be associated with a lower recurrence rate. However, these studies had some limitations: they were not prospective trials, there was limited information about the HH diameters or subtypes and there were no mid-term follow-up results.…”
Section: Discussionmentioning
confidence: 93%
“…Among these papers were 10 literature reviews [9,[32][33][34][35][36][37][38][39][40], complemented with a meta-analysis in four [33,34,38,40]. These reviews described up to five randomized controlled trials [10,[41][42][43][44], 17 cohorts, case-control studies, or caseseries [11,[45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]. One paper described pilot data to a later published RCT [61], two were case-reports [62,63].…”
Section: Robot-assisted Antireflux Surgery; Review Of Literaturementioning
confidence: 99%